Creating and Developing Geographical Thinking in Minors (Journal of Education and Development, 2025)
Humans are born with all their inherent abilities, which begin to emerge and develop through the support and guidance of adults in the family. This article explores how a child’s abilities are identified and shaped in harmony within the environment they live in. This environment can be categorised into distinct settings such as family, kindergarten, school, university, and society. Each of these plays a unique role in nurturing the child’s potential. However, the most crucial environment lies within the child’s own inner world. Through their desires and emotions, children observe and interpret their surroundings, refine their abilities, recognise patterns, and cultivate geographical thinking. The discovery of a child’s abilities is deeply influenced by the education, worldview, character, life experience, desires, and attitudes of the adults around them. The article illustrates how it is possible to foster a protective attitude towards nature and its resources while simultaneously developing geographical thinking. From an early age, children display research skills and begin to comprehend spatial environments. As they mature, this knowledge and skillset evolves into geographical thinking—a foundation for the modern vision of a green and peaceful planet.